Técnicas y herramientas de auditoría de sistemas interna en tiempos de pandemia (2021)
Given the pandemic propagated by Covid-19 that affected activities at a general level in Colombia, the objective of this article is to present the techniques and tools of systems auditing most used in Colombia during the COVID-19 pandemic. With the goal of understanding the way in which the audit activities are carried out remotely, given the impossibility of carrying them out in person due to the health emergency presented.